Highest Recorded Serum Creatinine - Christine Persaud; Uttsav Sandesara; Victor Hoang; Joshua Tate; Wayne Latack; David Dado (Case Reports in Nephrology)
Serum creatinine is a commonly used laboratory marker to assess kidney function; however, there has not been an established level of serum creatinine to predict mortality. After extensive literature review, we present a case of the highest recorded serum creatinine of 73.8 mg/dL in a 23-year-old male with the history of pediatric deceased donor kidney transplant (DDKT). He initially presented with uremia and signs of acute renal allograft failure after two months of immunosuppressive medication nonadherence, ultimately requiring emergent hemodialysis, which was complicated by new onset seizures. This was the patient’s fourth episode of late acute rejection and emphasizes the need for education of immunosuppressant adherence and periodic monitoring of renal function in high-risk patients. Though there is no known creatinine level incompatible with life, this patient appears to have the highest known serum creatinine in a uremic patient on record.